Micronucleus and chromosome aberrations induced in onion (Allium cepa) by a petroleum refinery effluent and by river water that receives this effluent - Hoshina, Marcia M. [UNESP]; Marin-Morales, Maria A. [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
In this study, micronucleus (MN) and chromosome aberration (CA) tests in Allium cepa (onion) were carried out in order to make a preliminary characterization of the water quality of the Atibaia River in an area that is under the influence of petroleum refinery and also to evaluate the effectiveness of the treatments used by the refinery. For these evaluations, seeds of A. cepa were germinated in waters collected in five different sites related with the refinery in ultra-pure water (negative control) and in methyl methanesulfonate solution (positive control). According to our results, we can suggest that even after the treatments (physicochemical, biological and stabilization pond) the final refinery effluent could induce chromosome aberrations and micronucleus in meristematic cells of A. cepa and that the discharge of the petroleum refinery effluents in the Atibaia River can interfere in the quality of this river. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Chromosome aberrations; Micronucleus; Allium cepa; Petroleum refinery effluents; Polluted river water